Analysis of Management Accounting Information System Characteristics in Supporting Financial Performance Achievement at PT. Bank Rakyat Indonesia Manado Branch Office - Anastasia Chandra; Hendrik Manossoh; Meily Kalalo (PT FORMOSA CENDEKIA GLOBAL, 2024)
Management accounting information systems play a role in helping managers identify problems, resolve problems, and evaluate performance. This information refers to the process of continuous value improvement in increasing the value of either a product or service. This research aims to determine the characteristics of the management accounting information systems applied at PT. Bank Rakyat Indonesia Manado Branch Office in supporting the achievement of financial performance. The type of research used is qualitative descriptive research and reseach data collection is carried out by means of interviews, observation, and documentation. The research results show that the management accounting information owned by PT. Bank Rakyat Indonesia Manado Branch Office, namely information that has the characteristics of broad scope, timeliness, aggregation, and integration has been carried out will which really helps management manage existing information, especially in decision making and helps in improving financial performance for the better.